Innovative Approaches to Teaching Biology Through Educational and Methodological Developments - Komilova Baxmal Odilovna; Jumaeva Ozoda Qalandarovna (Scientific Trends, 2024)
This article provides an in-depth analysis of innovative approaches to the use of educational and methodological developments in teaching biology. It examines the types of educational and methodological materials, their role and significance in the educational process, as well as their integration with modern technologies and interactive methods. The author highlights the effectiveness of using digital technologies, the STEAM approach, laboratory work, and visual aids in teaching biology, emphasizing their importance in increasing students' interest and strengthening their knowledge.
Keywords: Biology education, educational and methodological developments, innovative approaches, digital technologies, STEAM, laboratory work, interactive methods, visual aids, teaching efficiency.